KAITAN FILSAFAT PERENIALISME DAN PROGRESIVISME DENGAN ILMU KEGURUAN BAHASA DALAM MENGEMBANGKAN TATA BAHASA PEDAGOGIS UNTUK PEMBELAJARAN BAHASA - Tanjung, Hasian Romadon (JURNAL EDUCATION AND DEVELOPMENT, 2025)
Perenialist philosophy that emphasizes values and norms will not be in line with progressivism flow which always emphasizes new things. In learning process of a language, both flows have related values and norms with a better quality of learning. Teaching language needs guiding norms and values that are inseparable from the goals of quality education and learning, so the both philosophies are related. This research uses qualitative by applied literature study and content analysis. Literature search and references are the main elements in this writing activity. The results of the research are the main basic in reviewing and discussing the finding conceptually. It takes an active, interactive and fun learning process with the aim of educational success with basis of clear thinking based on ontological, epistemological and axiological. The application of language research methods aims to find out the problem solutions that encountered in language studies. Pedagogical studies in language teaching science are more specific in teaching and learning language. Pedagogical grammar is related to the teacher's way in teaching language to students or language learners. The purpose of language learning which concerns to four aspects of language skills which is contained in the curriculum set by the government. The learning that expected by language teachers is of course adapted to principles and norms of clear philosophical. This is intended so students are able to communicate properly and correctly and avoid language errors which include errors in spoken or written language based on clear ontological, epistemological, and axiological studies.